Unbalanced thermal field assisted thermo-compensated resistance brazing welding 6061 aluminum alloy to 304 stainless steel - Jiang Yu; Rongmao Du; Yanlong Fan; Hongtao Zhang (Journal of Materials Research and Technology, 2023)
The reliable Al/steel resultant welded joint with a large contact area was of great significance in electrolysis cells to produce aluminum. Herein, a large-area 6061 aluminum alloy/304 stainless steel dissimilar welds were successfully obtained by unbalanced thermal field assisted thermo-compensated resistance brazing welding(abbreviated as UTC-TC-RBW). In the present study, the heating distribution conditions of the joint were adjusted based on the introduction of the auxiliary welding current, forming an unbalanced temperature field. The whole welding temperature field of the joint was improved significantly with the increase of the auxiliary current, which promoted the interdiffusion of Al and Fe elements at the interface. Hence, the connection area between Al alloy and steel was increased gradually. The final interface between Al alloy and steel was changed to the Al(s.s) diffusion layer and Fe2Al5 layer. XRD results proved the presence of these phase compositions. When the auxiliary current was 0.3 kA, the maximum thickness of the Al(s.s) diffusion layer and Fe2Al5 layer reached 5.25 μm and 0.86 μm. The final load of the obtained joint with the auxiliary current of 0.3 kA was the maximum and reached 1789.7N, which was approximately 3 times that of the joints without auxiliary current.